Identification of Microflora Diversity and Its Influence on the Organoleptic Quality of the Traditional Dayak Food Tempoyak in Central Kalimantan - Swestyani, Sondra; Hujjatusnaini, Noor (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2023)
Tempoyak is a traditional fermented food of the Dayak ethnic group in Central Kalimantan. The production of tempoyak remains highly traditional and lacks innovation. Research on tempoyak is still limited, resulting in a lack of documentation of this food as part of Indonesia’s local wisdom and cultural heritage. Therefore, exploring preferences and the appeal of tempoyak’s organoleptic qualities among the millennial generation is essential. This study employed a one-shot case study design. The variables examined include the diversity of microflora in tempoyak and its effect on organoleptic quality and the level of preference among millennials. Isolate identification was conducted using API-50CHL, biochemical tests, and physiological tests. Organoleptic quality was assessed using a hedonic scale. A total of 120 panelists participated in the study, consisting of individuals from Dayak, Madurese, Javanese, and Banjar ethnic groups. Data were analyzed using one-way ANOVA. The study identified 15 microflora isolates in tempoyak that influence its taste and organoleptic properties, including 8 lactic acid bacteria isolates: Pediococcus acidilactici, Lactobacillus curvatus, Leuconostoc mesenteroides, Lactobacillus plantarum, Streptococcus thermophilus, Lactobacillus pentosus, Enterococcus faecium, and Weissella paramesenteroides; 1 non-lactic acid bacterium isolate (Micrococcus varians); 2 yeast isolates (Saccharomyces cerevisiae and Kluyveromyces marxianus); and 4 mold isolates, including Rhizopus, Monilia sitophila, and Mucor roxii. All identified microflora could produce lactic acid, except Aspergillus repens. Statistical analysis showed a significant effect on all sub-variables of organoleptic quality—color, taste, aroma, and texture of Tempoyak. These findings suggest a preference for the color and texture, and a liking for the taste and aroma of Tempoyak. The study indicates potential for Tempoyak to be further developed in a more innovative and contemporary manner, making it more appealing to the millennial generation.Keywords: tempoyak, organoleptic, microflora, Dayak